2022
DOI: 10.1021/acs.jafc.2c04063
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanism of Theaflavins in Regulating Skeletal Muscle Inflammation

Abstract: Persistent inflammatory infiltration of skeletal muscle is a principal trigger for the loss of muscle mass and strength. Theaflavins, the main functional components of black tea, have effects on muscle health, but their biological effects on skeletal muscle inflammation are unclear. We constructed in vitro and in vivo models of muscle inflammation and found that theaflavins reduced the expression of inflammatory factors (IL-1β, IL-6, and TNF-α) by regulating the TLR4/MyD88/NF-κB signaling pathway to alleviate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…In addition, the total theaflavins were significantly higher in the AOT-10 group than those in the other groups. The significant biological effects of the four theaflavin monomers on inflammation and maintenance of intestinal homeostasis in vivo were also demonstrated by Liu et al (Changwei Liu et al, 2022 ). Polysaccharides and flavonoids have been shown to alleviate colitis by inhibiting the expression of inflammatory factors and modulating the gut microbiota (F. Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the total theaflavins were significantly higher in the AOT-10 group than those in the other groups. The significant biological effects of the four theaflavin monomers on inflammation and maintenance of intestinal homeostasis in vivo were also demonstrated by Liu et al (Changwei Liu et al, 2022 ). Polysaccharides and flavonoids have been shown to alleviate colitis by inhibiting the expression of inflammatory factors and modulating the gut microbiota (F. Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 64%
“…Since TF1 inhibited the expression and activity of Sly, it was easy to explain why the adherence activity of TF1-treated SC19 was decreased. TF1 had anti-inflammatory activity in various models, such as cell, muscle, and brain [ 35 , 36 , 37 ]. A previous study revealed that TF1 reduced the expression of inflammatory factors (IL-1β, IL-6, and TNF-α) by regulating the TLR4/MyD88/NF-κB signalling pathway to alleviate muscle inflammation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…TF1 had anti-inflammatory activity in various models, such as cell, muscle, and brain [ 35 , 36 , 37 ]. A previous study revealed that TF1 reduced the expression of inflammatory factors (IL-1β, IL-6, and TNF-α) by regulating the TLR4/MyD88/NF-κB signalling pathway to alleviate muscle inflammation [ 36 ]. Lun et al demonstrated that Sly triggered TNF-α production in human monocytes and IL-6 production in pig PAM cells and monocytes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates the beneficial effect of theaflavins even in the presence of inflammatory infiltration in muscle. In fact, Liu et al (2022) performed in vitro and in vivo models of muscle inflammation and claim that theaflavins reduce the expression of inflammatory factors like IL-1β, IL-6 and TNF-α [58]. Aizawa et al (2017) also studied the beneficial effect of theaflavins on body fat and muscle in healthy individuals in a RCT.…”
Section: Therapeutical Approachesmentioning
confidence: 99%
“…In vitro and in vitro ↑PPAR-g expression of FABP4 Park SH et al [55] 2020 Quercetin In vivo and in vitro The gene expression of atrogin-1 and MuRF1 and phosphorylation of AMPK Suzuki K et al [57] 2020 Theaflavins In vivo Anabolic Akt/mTOR pathway; phosphorylation of 4EBP-1 Liu C et al [58] 2022 Theaflavins In vivo and in vitro Expression of IL-1β, IL-6 and TNF-α by regulating the TLR4/MyD88/ NF-κB signalling pathway Aizawa T et al [59] 2017 Theaflavins Pilot study Theaflavin had a beneficial effect on body fat and muscle Fujiwara Y et al [60] 2017 Oleuropein RCT ↑Traslocation of GLUT4 by activation of adenosine monophosphate-activated protein kinase (AMPK) Razaei S [61] 2018 Olive oil RCT ↓Body fat mass, not reduced the skeletal mass Santini SJ et al [62] 2020 Oleuropein In vivo and in vitro ↓Fat in HepG2 cells ↓IL1-α and G-CSF ↑SOD2 cytosol expression Santini SJ et al [63] 2022 Oleuropein In vivo and in vitro ↓fat in HepG2 cells ↓copper content of FA-HepG2 Less body and liver weight; Improved the level of transaminases and lipid profile Porcu C et al [64] 2018 Oleuropein In vivo and in vitro ↑Activation of Akt/ULK1 pathway can improve the pro-inflammatory and antioxidant 'defence state' in a mouse model of NAFLD [62,63]. Furthermore, the oral administration of Ole in C57BL/6 J mice on an unhealthy diet induced the activation of autophagy characterized by AMPK-dependent phosphorylation of ULK1 at Ser555, regardless of sex [64], (Table 1).…”
Section: In Vitromentioning
confidence: 99%